Survival in different habitats: Extreme ultramafic and calcareous soils affect Stachys recta essential oils composition. (4th July 2019) - Ascrizzi, Roberta; Maccioni, Simonetta; Bedini, Gianni; Flamini, Guido
Abstract: Two populations of Stachys recta growing in Italy on ultramafic and calcareous soils have been studied for their essential oils. Although the yields were comparable, the composition of the essential oils differed significantly. Plants growing on ultramafic soil produced mainly non-terpene derivatives (55.7%), of which the most abundant ones were 1-octen-3-ol (38.2%) and (E) -3-hexen-1-ol (5.9%); the terpenes α-cadinol (6.1%) and δ-cadinene (5.6%) were also significantly represented. In contrast, the populations living on calcareous soil produced an essential oil dominated by terpenes (93.8%), with germacrene D (18.8%), β-caryophyllene (17.7%), 1, 8-cineole (15.9%) and α-pinene (14.2%) among the main components.